The right to migrate: a matter of freedom or justice? - Niño Arnaiz, Borja (Daimon Revista Internacional de Filosofia, 2025)
Abstract: This paper investigates one of the central questions in the ethics of migration: is migration a matter of freedom or justice? The former claims that it is a human right, whereas the latter defends a remedial right to immigrate as a way to meet the requirements of global distributive justice. These arguments seem to enter into an intractable contradiction. On the one hand, if freedom of movement is a human right, it should not be subordinated to the maximization of justice. On the other hand, in a non-ideal world an open-borders policy would be of little help in the assignment of priorities, and its redistributive effects would be suboptimal. The solution, I will argue, lies in a package of global redistributive measures. More open borders now can bring us closer to justice, and only then would immigration make sense as a human right. Resumen: Este trabajo investiga una de las preguntas centrales en la ética de las migraciones: ¿son las migraciones una cuestión de libertad o de justicia? El primero reivindica la inmigración como un derecho humano, mientras que el segundo defiende un derecho subsidiario a inmigrar como forma de satisfacer las demandas de justicia distributiva global. Estos argumentos parecen entrar en una contradicción irresoluble. Por un lado, si la libertad de movimiento es un derecho humano, no debería subordinarse a la maximización de la justicia. Por otro lado, en un mundo no ideal una política de fronteras abiertas serviría de poca ayuda a la hora de asignar prioridades, y sus efectos redistributivos serían subóptimos. La solución, sostendré, pasa por un paquete de medidas redistributivas globales. Unas fronteras más abiertas en la actualidad pueden ayudarnos a avanzar en la senda de la justicia, momento en el cual cobraría sentido la inmigración como derecho humano.